2005
DOI: 10.1143/jjap.44.2701
|View full text |Cite
|
Sign up to set email alerts
|

Programming Characteristics of Phase Change Random Access Memory Using Phase Change Simulations

Abstract: We present a new simulation methodology for analyzing programming characteristics of a chalcogenide based phase-change device, phase change random access memory (PRAM), which is a next-generation non-volatile memory. Using the new simulation methodology, we analyze the initialization of chalcogenide material (ICM) of the mechanism and propose the next generation PRAM scheme. From the results of the phase change simulation, the process conditions for ICM for stable operation are presented. Also, the self-heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Two general categories of cell structures exist for implementing a sublithographic aperture. One category involves the control of this cross-section by the size of one of the electrical contacts to the phase-change material [contact minimized, Figure 1 [13,21,24], as well as the possibility for enhanced endurance. This possibility is supported by the observation that many failure and degradation mechanisms for PCRAM cells are associated with the interface between the phase-change material and one of the surrounding materials [27].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Two general categories of cell structures exist for implementing a sublithographic aperture. One category involves the control of this cross-section by the size of one of the electrical contacts to the phase-change material [contact minimized, Figure 1 [13,21,24], as well as the possibility for enhanced endurance. This possibility is supported by the observation that many failure and degradation mechanisms for PCRAM cells are associated with the interface between the phase-change material and one of the surrounding materials [27].…”
Section: Figurementioning
confidence: 99%
“…Because of the large number of factors that can influence the RESET current, predictive numerical simulations are important. A number of studies have used analytical equations [28][29][30][31], finite-element techniques [21,[32][33][34], and finite-difference techniques [6,35] to analyze either PCRAM cells or the phase-change material. Pirovano et al [13] studied the RESET current and the thermal proximity effect of scaled PCRAM using both simulation and experiment.…”
Section: Figurementioning
confidence: 99%
“…Phase change random access memory (PCRAM) is one of the highly promising next-generation memories by virtue of its nonvolatile data retention property and rapid writing and reading speeds. However, high reset current has been a major obstacle to further scaling of PCRAM, and it has been suggested that confining the phase change materials into a very narrow trench or hole, a so-called confined cell, could be a viable method to solve the high reset current problem. For such confined cell structures, it is necessary to deposit the Ge 2 Sb 2 Te 5 film, which is the most suited phase change material (PCM) for memory devices, using a process that offers excellent conformality in terms of its thickness as well as its chemical composition, such as atomic layer deposition (ALD).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have used analytical equations [49,108,[119][120][121][122], finite-element techniques [123][124][125][126][127][128][129][130][131], and finite-difference techniques [42,132] to analyze either PCM cells or phase change material. Pirovano et al studied the RESET current and the thermal proximity effect of scaled PCM by both simulation and experiment [41].…”
Section: Modeling Of Pcm Physics and Devicesmentioning
confidence: 99%

Phase change memory technology

Burr,
Breitwisch,
Franceschini
et al. 2010
Preprint